Impact of eight weeks of plyometric training on jump parameters in junior badminton players - Felder, H.; Fröhlich, M.; Reuter, R. (World Badminton Federation, 2016)
Plyometric training is popular among individuals involved in dynamic sports, and plyometric exercises such as jumping, hopping, skipping and bounding are executed with the goal of increasing dynamic muscular performance, especially jumping. Much less information is available on the effectiveness of plyometric training (PT) in badminton, where jumping height (e.g. forehand overhead jump-smash) is important for success. The aim of the study was to investigate the effects of an eight-week periodized PT program on jumping height, agility and power among male and female junior badminton players, using high-impact bilateral plyometric exercises.